2020
DOI: 10.3390/ijms21030825
|View full text |Cite
|
Sign up to set email alerts
|

Tight Junction Proteins and the Biology of Hepatobiliary Disease

Abstract: Tight junctions (TJ) are intercellular adhesion complexes on epithelial cells and composed of integral membrane proteins as well as cytosolic adaptor proteins. Tight junction proteins have been recognized to play a key role in health and disease. In the liver, TJ proteins have several functions: they contribute as gatekeepers for paracellular diffusion between adherent hepatocytes or cholangiocytes to shape the blood-biliary barrier (BBIB) and maintain tissue homeostasis. At non-junctional localizations, TJ pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 173 publications
(214 reference statements)
1
43
0
Order By: Relevance
“…Morphology of HepG2 cells was shown to keep main features of the hepatocytes: tight junctions separate apical and basolateral plasmalemma providing formation of bile capillaries and blood-biliary barrier; ultrastructural observations were supported by immunohistochemical and biochemical studies [ 38 , 39 ]. Based on current knowledge about the role of tight junctions in hepatic physiology and pathology, it is possible to claim that formation of these structures by HepG2 cells evidences for high levels of differentiation [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Morphology of HepG2 cells was shown to keep main features of the hepatocytes: tight junctions separate apical and basolateral plasmalemma providing formation of bile capillaries and blood-biliary barrier; ultrastructural observations were supported by immunohistochemical and biochemical studies [ 38 , 39 ]. Based on current knowledge about the role of tight junctions in hepatic physiology and pathology, it is possible to claim that formation of these structures by HepG2 cells evidences for high levels of differentiation [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The TJ barrier controls the diffusion of molecules by acting as semipermeable diffusion barriers through the paracellular pathway. It has been reported that transmembrane proteins such as claudin and occludin are essential for the regulation of paracellular permeability (Balda & Matter, 2000;Lee, 2015;Roehlen et al, 2020). ZO-1 is also responsible for the regulation of paracellular permeability (i.e., permeability for the passage of molecules between adjacent epithelial cells) via TJ complexes as it binds directly to transmembrane proteins (Balda & Matter, 2000;Lee, 2015;Roehlen et al, 2020).…”
Section: Zonula Occludens (Zo) Proteinsmentioning
confidence: 99%
“…It has been reported that transmembrane proteins such as claudin and occludin are essential for the regulation of paracellular permeability (Balda & Matter, 2000;Lee, 2015;Roehlen et al, 2020). ZO-1 is also responsible for the regulation of paracellular permeability (i.e., permeability for the passage of molecules between adjacent epithelial cells) via TJ complexes as it binds directly to transmembrane proteins (Balda & Matter, 2000;Lee, 2015;Roehlen et al, 2020). Loss of ZO-1 can retard the formation of the TJ complexes, and further breakdown of ZO-1 may result in severe disruption of the paracellular barrier in epithelial cells (Roehlen et al, 2020).…”
Section: Zonula Occludens (Zo) Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TJ barrier controls the diffusion of molecules by acting as semipermeable diffusion barriers through the paracellular pathway. It has been reported that transmembrane proteins such as claudin and occludin are essential for the regulation of paracellular permeability (Balda & Matter, 2000;Lee, 2015;Roehlen et al, 2020). ZO-1 is also responsible for the regulation of paracellular permeability (i.e.…”
Section: Zonula Occludens (Zo) Proteinsmentioning
confidence: 99%